Bauran Pemasaran Jasa Pendidikan (Metakognisi, 2025)
The marketing mix of educational services is an important strategy used by educational institutions to attract and retain the interest of prospective students amidst increasingly fierce competition. This study identified seven main elements in the marketing mix, namely product, price, place, promotion, people, physical evidence, and process. Each element contributes significantly to the perception and decision of prospective students in choosing an educational institution. By focusing on curriculum innovation, competitive pricing, strategic location, and effective promotion through social media, educational institutions can increase their attractiveness. In addition, the quality of teaching staff and adequate physical facilities also play an important role in creating a positive experience for students. The implementation of a comprehensive marketing mix strategy can not only increase the number of registrants but also build a strong reputation in the education market. This study is expected to provide insight for educational institution managers in formulating more effective and responsive marketing strategies to student needs.